Growth Strategy for Start-Up Businesses: Analysis of Solutions for Scalability, Marketing, and Risk Management - Yuwono, Imam; Rakhmawati, Nur Endah; Putri, Nurulita Purnama (Universitas Mercu Buana, 2024)
Start up businesses experiencing difficulties in their growth process, especially in terms of scalability, marketing, and risk management. Scalability is the ability of a business to increase its operational scale without reducing efficiency and effectiveness. Marketing is the process of promoting a product or service so that it is known to the public and attracts consumer interest. Risk management is an action taken by the company to reduce the negative impact of unwanted events. Based on this background, research will be carried out entitled: